BVLOS UAS Operations in Highly-Turbulent Volcanic Plumes - Wood, Kieran; Liu, Emma J.; Richardson, Tom; Clarke, Robert; Freer, Jim; Aiuppa, Alessandro; Giudice, Gaetano; Bitetto, Marcello; Mulina, Kila; Itikarai, Ima (Frontiers in Robotics and AI, 2020)
Long-range, high-altitude Unoccupied Aerial System (UAS) operations now enable in-situ measurements of volcanic gas chemistry at globally-significant active volcanoes. However, the extreme environments encountered within volcanic plumes present significant challenges for both air frame development and in-flight control. As part of a multi-disciplinary field deployment in May 2019, we flew fixed wing UAS Beyond Visual Line of Sight (BVLOS) over Manam volcano, Papua New Guinea, to measure real-time gas concentrations within the volcanic plume. By integrating aerial gas measurements with ground- and satellite-based sensors, our aim was to collect data that would constrain the emission rate of environmentally-important volcanic gases, such as carbon dioxide, whilst providing critical insight into the state of the subsurface volcanic system. Here, we present a detailed analysis of three BVLOS flights into the plume of Manam volcano. Specifically, we discuss the challenges involved in operating in highly turbulent volcanic plumes. A detailed description of the system is presented, including ground and air components, and flight plans. We present logged flight data for two successful flights to evaluate the aircraft performance under the atmospheric conditions experienced during plume traverses. Further, by reconstructing the sequence of events that led to the failure of the third flight, we identify a number of lessons learned and propose appropriate recommendations to reduce risk in future flight operations.